2018
DOI: 10.3390/w10060769
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Distribution of TSS Event Loads from Small Urban Environments

Abstract: Results from a long-term stormwater quality monitoring program were used to derive total suspended solids (TSS) event load distributions at four small urban environments (flat roof, parking lot, residential catchment, high traffic street). Theoretical distribution functions were fitted to the empirical distribution functions obtained. Parameters of the theoretical distribution functions were optimized with respect to a likelihood function to get both optimized parameters and standard errors. Kolmogorov-Smirnov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Several empirical equations and models have commonly been used in the literature to model urban wash-off 3,[8][9][10] . However, the prediction accuracy of these lumped formulations is still quite limited 11,12 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Several empirical equations and models have commonly been used in the literature to model urban wash-off 3,[8][9][10] . However, the prediction accuracy of these lumped formulations is still quite limited 11,12 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Instead of replicating single-event characteristics or pollutographs, the approach aims to minimize the difference between observed and simulated TSS event load distribution. Since observed TSS event load distributions can be well approximated with theoretical distribution functions [22], the calibration uses a site-specific parameterized lognormal distribution as reference (cf. Section 2.3).…”
Section: Concept Of Model Calibrationmentioning
confidence: 99%
“…Leutnant et al [22] use TSS event load data from Leutnant et al [24] and describe site-specific empirical TSS event load distributions by means of theoretical distribution functions. The authors demonstrated that the two-parameter lognormal distribution approximates the empirical TSS event load distribution well and can therefore be used to probabilistically describe TSS event loads.…”
Section: Theoretical Distribution Function For Site-specific Tss Evenmentioning
confidence: 99%
See 2 more Smart Citations